Spontaneous emission from semiconductor nanocrystals in coupled spherical microcavities - Donegan, John; Bradley, Louise; Boland, John (My University, 2005)
We report on the coherent coupling of whispering gallery modes (WGM) in a photonic molecule formed from two melamine-formaldehyde spherical microcavities coated with a thin shell of light-emitting CdTe nanocrystals (NCs). Utilizing different excitation conditions the splitting of the WGM resonances originating from bonding and anti-bonding branches of the photonic states is observed and fine structure consisting of very sharp peaks resulting from lifting of the WGM degeneracy has been detected. Time-resolved measurements showed a slight increase in the spontaneous emission rate of NCs in a photonic molecule when compared to the spontaneous emission rate for NCs coating a single microsphere.
PUBLISHED